Skip-beat!. 29 - Nakamura, Yoshiki (Shojo beat manga., 2012)
Kyoko Mogami followed her true love Sho to Tokyo to support him while he made it big as an idol. But he's casting her out now that he's famous! Kyoko won't suffer in silence -- she's going to get her sweet revenge by beating Sho in show biz!